TESTING THE ADAPTIVE MARKET HYPOTHESIS (AMH) AS AN EVOLUTIONARY PERSPECTIVE ON MARKET EFFICIENCY BY SIMPLE MOVING AVERAGE (SMA) METHOD (CAHIERS MAGELLANES-NS, 2024)
In the realm of financial markets, experts have extensively employed technical analysis. Especially, certain academic investigations have underscored the capacity of these tools to yield favorable returns in comparison to a straightforward buy-and-hold approach. Our study examined BSE Sensex, Brazilian Index, Financial Times Stock Exchange Group (FTSE), German DAX, Hang Seng Index, Standard and Poor's (S&P 500), and Nikkei 225. During the timeframe spanning from 1998 to 2023, a practical implication derived from the Adaptive Market Hypothesis (AMH) is that profit opportunities materialize intermittently, depending upon the level of market efficiency and the prevailing market circumstances. To probe into this implication, we systematically monitor the evolving efficacy of simple moving average trading strategies, along with the correlation between this efficacy and both the degree of market efficiency and specific market conditions. The major findings reveal that investing at maxima and minima of simple moving average result in more favorable outcomes than a passive buy and hold strategy. Consequently, investors possess the opportunity to leverage market inefficiencies and particular market conditions through trading strategies such as directional trading. In aggregate, our findings and results align with the framework of the Adaptive Market Hypothesis (AMH), which has been validated as a superior explanatory model for the dynamics of emerging markets in comparison to the Efficient Market Hypothesis (EMH).